2013
DOI: 10.1111/nure.12031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional challenges and health implications of takeaway and fast food

Abstract: Nutritional challenges and health implications of takeaway and fast foodhttp://researchonline.ljmu.ac.uk/6791/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private study or for non-commercial research. You … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
146
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 93 publications
(215 reference statements)
4
146
0
5
Order By: Relevance
“…The energy density, defined as the energy content per unit weight of foods, meals or diets (26) , of fast food may also be important, since individuals consume a relatively constant weight of food and therefore consumption of foods with high energy density may lead to a passive increase in energy intake (25) . Experiments have also shown that energy-dense diets challenge the innate ability to maintain energy homeostasis (26) .…”
Section: Discussionmentioning
confidence: 99%
“…The energy density, defined as the energy content per unit weight of foods, meals or diets (26) , of fast food may also be important, since individuals consume a relatively constant weight of food and therefore consumption of foods with high energy density may lead to a passive increase in energy intake (25) . Experiments have also shown that energy-dense diets challenge the innate ability to maintain energy homeostasis (26) .…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prominent trends is the increase in outside food consumption (Jaworowska et al, 2013). In many countries, restaurants especially fast food outlets have been criticized by nutritionists, health crusaders and the media over its offering of high-fat foods (Totten et al, 2009), and its impact on obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses provide convincing evidence that replacing SFA with PUFA reduced CVD risk and coronary heart disease (CHD) events (Flock et al, 2014;Mozaffarian et al, 2010). SFA intake has recently shown a reduction in the UK population (Pot et al, 2012) but dietary recommendations have still not been met and food eaten out of the home has increased (Jaworowska et al, 2013). From the present study both the English and pizza meal categories had the highest amount of SFA with a median average of 35.7 g/portion each (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide consumer patterns over the last 10 years have led to lifestyle changes around food intake with a higher reliance on food eaten out of the home, including takeaway food (Guthrie et al, 2002;Jaworowska et al, 2013;Naska et al, 2011;Naska et al, 2015;Orfanos et al, 2007;Smith et al, 2009;Food Standards Agency (FSA), 2007). While there are no formal definitions of takeaway food we describe takeaway food as hot meals, prepared in situ, either taken away or consumed on site from nonchain, independent establishments.…”
Section: Introductionmentioning
confidence: 99%